Nine Gems of the Speciality and Ten Commandments for Specialists in Oral Medicine and Radiology - N Gnanasundaram (Wolters Kluwer Medknow Publications, 2006)
A few doctors both in Medicine and Dentistry ask, 'what is Oral Medicine?' What are you doing? A few people ask, Does Oral Medicine means? giving Medicine orally? A few administrators ask how exactly Oral Medicine should be accomodated in the Dental College, what are their responsibilities? A few people of social organizations ask - Do the Oral Medicine expert have any responsibility in community service? A few scientists and researchers are doubt whether there are any research aspects in Oral Medicine. The glory of "Oral Medicine and Radiology - A recognized speciality by the Dental Council of India", (ever since the syllabus was formed) and the charm of services both in academics and society by the Oral Medicine experts have not been properly understood by a few sections of people. Hence, details of this speciality have been written here under 9 headings as NINE GEMS and the yeomen services of Oral Medicine and Radiology experts are explained as the TEN COMMANDMENTS in this article. I request my colleagues and my students to speak loudly, explain politely and make the people understand our speciality and our responsibility to the community at large.